Introduction: Cross-cultural articulations of war magic and warrior religion - Farrer, Douglas S. (Social Analysis, 2014)
Previous anthropology emphasized symbolic incantations at the expense of the embodied practice of magic. Foregrounding embodiment and performance in war magic and warrior religion collapses the mind-body dualism of magic versus rationality, instead highlighting social action, innovation, and the revitalization of tradition, as tempered historically by colonial and post-colonial trajectories in societies undergoing rapid social transformation. Religion and magic are re-evaluated from the perspective of the practitioner's and the victim's embodiment in their experiential life-worlds via articles discussing Chinese exorcists, Javanese spirit siblings, Sumatran black magic, Tamil Tiger suicide bombers, Chamorro spiritual re-enchantment, tantric Buddhist war magic, and Yanomami dark shamans. Central themes include violence and healing, accomplished through ritual and performance, to unleash and/or control the power of gods, demons, ghosts and the dead. © Berghahn Journals.
Created from Fastlane, Scopus look-up
Keywords: Embodiment; Magic; Performance; Shamanism; Sorcery; Violence; Warfare; Witchcraft